The Role Of Literary Education Methods In Teaching Creative Life And Creativity - USMONOVA, OYISTAKHON; KUDRATKHODJAEVA, NARGIS; USMONOVA, ZULKHUMOR; GIYASOVA, NIGORA (The journal of contemporary issues in business and government, 2021)
In Uzbekistan, the experience of teaching literary sciences has existed for several hundred years. Our people, who pay great attention to the teaching of language and literature, have always been interested in the teaching and learning of these areas. The main reason for this is that the Uzbek people have been paying special attention to fiction for centuries and are very interested in art. At different stages of education, not only the age characteristics of the student but also the genre and style of the work require specific approaches to teaching and learning. There are also specific methods of literary education in higher education. Teaching methods in philological education today are based on traditional and non-traditional methods.